Scales Used to Measure Job Stressors in Intensive Care Units: Are They Relevant and Reliable? A Systematic Review - Laurent, Alexandra; Lheureux, Florent; Genet, Magali; Martin Delgado, Maria Cruz; Bocci, Maria G.; Prestifilippo, Alessia; Besch, Guillaume; Capellier, Gilles (Frontiers in Psychology, 2020)
Background: Many studies have been conducted in intensive care units (ICUs) to identify the stress factors involved in the health of professionals and the quality and safety of care. The objectives are to identify the psychometric scales used in these studies to measure stressors and to assess their relevance and validity/reliability. Methods: All peer-reviewed full-text articles published in English between 1997 and 2016 and focusing on an empirical quantitative study of job stressors were identified through searches on seven databases and editorial portals. Results: From the 102 studies analyzed, we identified 59 different scales: 17 “all settings scales” (16 validated scales), 20 “healthcare settings scales” (13 validated scales), and 22 “ICU settings scales” (2 validated scales). All these scales used measured stressors from at least one of the following eight broad categories: High job demands, Problematic relationships with other professionals, Lack of control over work-situations and career, Lack of organizational resources, Problematic situations with users and relatives, Dealing with ethical- and moral-related situations, Risk management issues, and Disadvantages in comparison to other occupational situations. The “all settings scales” and “healthcare settings scales”, most often validated, did not measure, or only slightly measured, the stressors most specific to ICUs. Where these were taken into account, the authors were forced to develop their own tools or modify existing scales without testing the validity of the tool used. Conclusions : This review highlights the lack of a tool that meets both the criteria of validity and relevance with regard to the specificity of work in ICUs. Future research must focus on developing reliable/valid tools covering all types of relevant stressors to ensure the quality of the studies carried out in this field.